2003
DOI: 10.1186/1471-2229-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Sub-cellular trafficking of phytochemicals explored using auto-fluorescent compounds in maize cells

Abstract: Background: Little is known regarding the trafficking mechanisms of small molecules within plant cells. It remains to be established whether phytochemicals are transported by pathways similar to those used by proteins, or whether the expansion of metabolic pathways in plants was associated with the evolution of novel trafficking pathways. In this paper, we exploited the induction of green and yellow auto-fluorescent compounds in maize cultured cells by the P1 transcription factor to investigate their targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Then, similarly to other metabolites, the flavonoid allocation could occur through different parallel pathways, the details of which are still poorly understood. Microscopy analyses by Lin and co-workers [73] have shown that phytochemicals are transported by at least two distinct vesicle trafficking pathways, addressed either to cell wall or to vacuole. The first one is a trans Golgi network (TGN)-independent pathway, suggesting that it is different from the secretion pathway of most proteins.…”
Section: Transport Mediated By Vesicle Trafficking In Plant Cellsmentioning
confidence: 99%
“…Then, similarly to other metabolites, the flavonoid allocation could occur through different parallel pathways, the details of which are still poorly understood. Microscopy analyses by Lin and co-workers [73] have shown that phytochemicals are transported by at least two distinct vesicle trafficking pathways, addressed either to cell wall or to vacuole. The first one is a trans Golgi network (TGN)-independent pathway, suggesting that it is different from the secretion pathway of most proteins.…”
Section: Transport Mediated By Vesicle Trafficking In Plant Cellsmentioning
confidence: 99%
“…It could be further demonstrated that anthocyanins are transported to the cell wall or the vacuole by at least two distinct vesicle trafficking pathways (Lin et al, 2003). The first leads to the accumulation of anthocyanic vacuolar inclusions – the dark red- to purple-pigmented spherical bodies in vacuole known also as AVIs.…”
Section: Transport Mediated By Vesicle Trafficking In Plant Cellsmentioning
confidence: 99%
“…There are many low molecular weight substances derived from or related to phenylpropanoid metabolism—structurally so similar to anthocyanins, that it is reasonable to assume that at least some of them might be also transported in similar autophagy-related membrane containers. It was observed already, more than ten years ago, that phytochemicals with distinct autofluorescence accumulate within membranous bodies, which are differentially targeted to the vacuole or apoplast [30]. Some of these bodies resemble the branched tubular structures mentioned above.…”
Section: Endoplasmic Reticulum Initiated Autophagy As a General Pathwmentioning
confidence: 99%
“…In model Lithospermum erythrorhizon cells and hairy root cultures after synthesis in the ER, the membrane containers with shikonin are bound to the PM [56,57], allowing one to speculate also about a possible autophagy-related mechanism of this process. The most vivid example of possible autophagy-related exosome secretion was provided in maize cells; upon the induction of the P1 transcription factor, autofluorescent membrane-bound bodies (possibly ER derived) accumulate in the cytoplasm and fuse with the PM, releasing their autofluorescent content into the cell wall in an exosome-like manner [30]. Phenylpropanoids, such as hydroxycinnamic acid derivatives, are found in the cell walls esterified to the wall polysaccharides; they are synthesized at the ER, and from there, they are released in a small membrane vesicles, which aggregate into bigger structures, fusing with the PM and releasing the content into the apoplast [58].…”
Section: Putative Autophagy-related Export Of Secondary Metabolites Tmentioning
confidence: 99%